A homozygous loss‐of‐function mutation in PDE2A associated to early‐onset hereditary chorea. Issue 3 (2nd February 2018) - Salpietro, Vincenzo; Perez‐Dueñas, Belen; Nakashima, Kosuke; San Antonio‐Arce, Victoria; Manole, Andreea; Efthymiou, Stephanie; Vandrovcova, Jana; Bettencourt, Conceicao; Mencacci, Niccolò E.; Klein, Christine; Kelly, Michy P.; Davies, Ceri H.; et al.
ABSTRACT: Background: We investigated a family that presented with an infantile‐onset chorea‐predominant movement disorder, negative for NKX2‐1, ADCY5, and PDE10A mutations.Methods: Phenotypic characterization and trio whole‐exome sequencing was carried out in the family.Results: We identified a homozygous mutation affecting the GAF‐B domain of the 3', 5'‐cyclic nucleotide phosphodiesterase PDE2A gene (c.1439A>G; p.Asp480Gly) as the candidate novel genetic cause of chorea in the proband. PDE2A hydrolyzes cyclic adenosine/guanosine monophosphate and is highly expressed in striatal medium spiny neurons. We functionally characterized the p.Asp480Gly mutation and found that it severely decreases the enzymatic activity of PDE2A. In addition, we showed equivalent expression in human and mouse striatum of PDE2A and its homolog gene, PDE10A .Conclusions: We identified a loss‐of‐function homozygous mutation in PDE2A associated to early‐onset chorea. Our findings possibly strengthen the role of cyclic adenosine monophosphate and cyclic guanosine monophosphate metabolism in striatal medium spiny neurons as a crucial pathophysiological mechanism in hyperkinetic movement disorders. © 2018 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.